If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3-x=(1/4)97-x)-(1/3)(2x-3)
We move all terms to the left:
3-x-((1/4)97-x)-(1/3)(2x-3))=0
Domain of the equation: 4)97-x)!=0
x!=0/1
x!=0
x∈R
Domain of the equation: 3)(2x-3))+3!=0We add all the numbers together, and all the variables
x∈R
-x-((+1/4)97-x)-(+1/3)(2x-3))+3=0
We add all the numbers together, and all the variables
-1x-((+1/4)97-x)-(+1/3)(2x-3))+3=0
We multiply parentheses ..
-(+2x^2+1/3*-3))+3-1x-((+1/4)97-x)=0
We can not solve this equation
| 2x(6-50)(4+4)=4x(2+2)20 | | -3(3x-1)-3=4 | | 6x-57=180 | | 5n+7=4n+10 | | 1/2x+4=36 | | 70-3•x=46 | | (2x+7+x+74=180 | | 9x-3=9x+36 | | 8x+4=2(4x+) | | 0.2(c-3.7)=8.2 | | 6d-11/2=2d+13/2 | | 22-3f=10 | | r/13=17 | | -7+19x=19x-7 | | 4(p-6.5)=14 | | -3(s+91)=-27 | | (.30x)+x=10000 | | 6x^2+2x-14=49-45x | | 37-3v=16 | | 30.72=6(y+2.04) | | F(30)=3n-7 | | 25-6b=97 | | x=90-x+40 | | 7(z+214)=4347 | | -2(x+3)-4(3x+6)=19 | | m/6+25=29 | | x=40+x | | X+3=8x-9 | | x=40+ | | 2+9x-18=9-10x+1 | | F(n)=3n-7 | | 1572=3(b-400) |